Enhancing the Security of Data Using DES Algorithm along with Substitution Technique (International Journal of Engineering and Computer Science, 2016)
The security is important issue of the field of networking. Security is the initial stage of authentication and the authentication is highly influencing of modern cryptography. The Data encryption standard (DES) algorithm is a symmetric key algorithm for the using of encryption of electronic data and secure of information. The DES algorithm is provided security of brute force attack. To improve the security of DES algorithm using substitution technique is added before the DES algorithm to perform its process. The substitution cipher is the method of encoding by which unit of plaintext are replaced with cipher text. If the substitution technique is used before the original DES algorithm then the intruder required first to break the original DES algorithm and then substitution technique.